2012
DOI: 10.1002/elps.201200099
|View full text |Cite
|
Sign up to set email alerts
|

Fluid mixing using AC electrothermal flow on meandering electrodes in a microchannel

Abstract: The mixing of fluids using AC electrothermal flow (AC-ETF) is presented. A pair of coplanar electrodes with a sinusoidal interelectrode gap was used to enhance the mixing in a microchannel. To demonstrate the performance of the mixer, conventional dilution experiments were conducted using Texas Red-labeled dextran. The dependence of mixing on the salt concentration (10(-3) ∼ 10(-1) mol dm(-3) ) of the solutions and frequency (100 kHz ∼ 5 MHz) of the applied voltage were investigated. AC-ETF was responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 28 publications
1
56
1
Order By: Relevance
“…the electric, 22,23 magnetic, 24 and acoustic 25 fields in addition to others. Of late, theoretical and experimental studies on AC electrokinetics [26][27][28] have extended to AC electroosmosis (ACEO) 29,30 and AC electrothermal (ACET).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the electric, 22,23 magnetic, 24 and acoustic 25 fields in addition to others. Of late, theoretical and experimental studies on AC electrokinetics [26][27][28] have extended to AC electroosmosis (ACEO) 29,30 and AC electrothermal (ACET).…”
Section: Introductionmentioning
confidence: 99%
“…32 Although efficient ACET mixers were reported, several issues are remained to be addressed for the application in organs-on-a-chip systems. Ng et al 33 reported a micromixer that can be operated from the ACEO (r ¼ 1 mS/m) to the ACET (r ¼ 500 mS/m) with the voltage of 20 V. Sasaki et al 23 designed a pair of coplanar electrodes with a sinusoidal interelectrode gap to mix the fluids (r ¼ 1.29 S/m) with the voltage of 30 V. Wu et al 34 used ACET 3-D electrodes to mix the fluids (r ¼ 0.2-1 S/m) with the voltage of 42-51.75 V. The electric conductivity of cell culture medium is around 1.7 S/m, which is beyond the upper limit of the previous study of the ACET micromixer. Huge joule heat will be generated in cell culture medium with the high voltages in the above studies (V ¼ 20-51.75 V), which will damage the cells or destroy some of the protein in the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical study of ACET flow was proposed as actuation mechanism for mixing applications, with the same size of electrode pairs on the opposite side walls of a microchannel . A pair of coplanar electrodes with a sinusoidal inter‐electrode gap was investigated experimentally to enhance the mixing process inside a microchannel by ACET effects . Microfluidic chip consisted of a DC‐heating element and AC field electrodes arranged as ACET micropump with driving voltage below 5 V .…”
Section: Introductionmentioning
confidence: 99%
“…35 An improved design has also been reported recently (Figure 4B). 36 In this design, a pair of coplanar electrodes with a sinusoidal interelectrode gap was used to enhance the mixing in a microchannel.…”
Section: Microfluidic Operationsmentioning
confidence: 99%